2023
DOI: 10.1002/adhm.202302011
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Cell Culture Applications of Core‐Shell Hydrogel Fibers Composed of Chitosan/DNA Interfacial Polyelectrolyte Complexation and Calcium Alginate: Straight and Beaded Core Variations

Abstract: Core‐shell hydrogel fibers are widely used in cell culture applications. A simple and rapid method is presented for fabricating core‐shell hydrogel fibers, consisting of straight or beaded core fibers, for cell culture applications. The core fibers are prepared using interfacial polyelectrolyte complexation (IPC) with chitosan and DNA. Briefly, two droplets of chitosan and DNA are brought in contact to form an IPC film, which is dragged to prepare an IPC fiber. The incubation time and DNA concentration are adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Recently, Utagawa and others developed a rapid approach to generate a coreshell fibre, prepared from interfacial polyelectrolyte complexation (IPC), chitosan, DNA as core and Ca-alginate serving as shell (Figure 2A). The authors showed that the fibre shape can be changed by adjusting the concentration of DNA, providing an adequate environment for HepG2, 3T3, HUVECs, and 3T3 cells co-culturing (Utagawa et al, 2023).…”
Section: Microfluidic Spinning Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Utagawa and others developed a rapid approach to generate a coreshell fibre, prepared from interfacial polyelectrolyte complexation (IPC), chitosan, DNA as core and Ca-alginate serving as shell (Figure 2A). The authors showed that the fibre shape can be changed by adjusting the concentration of DNA, providing an adequate environment for HepG2, 3T3, HUVECs, and 3T3 cells co-culturing (Utagawa et al, 2023).…”
Section: Microfluidic Spinning Technologymentioning
confidence: 99%
“…FIGURE 2Different approaches in microfluidic 3D bioprinting: (A) Spun core-shell hydrogel fibre composed of chitosan/DNA IPC and the effect of Ca 2+ presence in chitosan or DNA on fibre length. Adopted with permission from(Utagawa et al, 2023). Hydrogel fibres with different diameter, microfluidic printhead to fabricate multiple material core extrusion for single-layer, multi-layer and hydrogel bundle printing with gradual color transition, Multilayered hydrogel bundles with variable core material fibres.…”
mentioning
confidence: 99%